Types and Abundance of Microplastics in African Catfish (Clarias gariepinus) from Sumber Agung Village, Parigi Moutong - Mudrikah Tus Sa'diah; Fatmah Dhafir; Masrianih; Sutrisnawati; Bustamin; Rafiqa (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine the types and abundance of microplastics in African catfish (Clarias gariepinus) collected from aquaculture ponds and a river in Sumber Agung Village. A descriptive research design was employed using both qualitative and quantitative approaches. A total of 10 catfish aged approximately two months were used as samples, consisting of five individuals from aquaculture ponds and five individuals from the river. Digestive tract samples were digested using 10% KOH solution for 96 hours to separate microplastic particles, followed by filtration, identification, and particle counting. The results showed that microplastics were detected in all catfish samples. Three types of microplastics were identified: fibers, films, and fragments. The abundance of microplastics in catfish from aquaculture ponds was 103.6 particles/individual, which was higher than that observed in catfish from the river, at 57.6 particles/individual. Fragments were the dominant microplastic type in pond-derived catfish, whereas fibers predominated in river-derived catfish. Differences in microplastic abundance were influenced by the characteristics of the aquatic environment, with ponds having limited water circulation that may facilitate microplastic accumulation. These findings indicate that catfish have the potential to serve as bioindicators of microplastic pollution in both aquaculture systems and natural freshwater environments. However, microplastic identification in this study was based solely on microscopic observation; therefore, the polymer composition of the detected microplastics could not be confirmed.